Data placement and management algorithms for data centers - Hua, Stephen Tran Dung. (2012)
The report presents the purpose, concept, technique, detail explanation, results and consideration of the project “Data Placement and Management Algorithms for Data Centers”. The project is part of a joint research of NTU School of Computer Engineering and School of Mathematics Science about “Self-Repairing Code”. The project developed a pioneer Website application which utilizes Projective Self-Repairing Code (PSRC) of the Self-Repairing Code family. It is to prove the correctness and applicableness of the PSRC for data distribution over the network. The code tries to deliver a new concept of an effective and efficient mechanism to recover data lost in a distributed system. Binary file is treated as data and according to this PSRC, the web application has achieved splitting file into parts, creating redundant parts, distributing these parts over the network storages, repairing any file part loss and reconstructing original file. The author has developed a dynamic interactive website with user-friendly features as a file repository system and implemented these abovementioned functionalities applying PSRC algorithm. The application is built using robust and adaptive VB.NET with rich library classes to manipulate binary file as well as utilize socket for file transmission over the network. The SQL database is used to assist in file’s information storage. Furthermore, techniques such as bitwise XOR and random selection of nodes are implemented to make the PSRC concepts possible. Error handling and software testing have been taken care of to make this a quality application. In conclusion, the project has built a quality online repository application which first ever realizes the PSRC.